53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-1717
|View full text |Cite
|
Sign up to set email alerts
|

A Study Based on the AIAA Aerodynamic Design Optimization Discussion Group Test Cases

Abstract: The fourth model problem from the AIAA Aerodynamic Design Optimization Discussion Group is studied, referred to below as the ADODG CRM wing test case. Two optimization software packages are utilized, TRANAIR design and MDOPT (using both Design of Experiments methods as well as gradient based methods) with OVERFLOW. The resulting designed and associated baseline geometries are cross-analyzed using OVERFLOW and TRANAIR. Previous results using TRANAIR design were run using standard engineering practices and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Meheut [20] compared a number of optimised aerofoil shapes from six different institutes [4,5,7,13,14,16] with the same flow solver. This produced a range of final drag results (all similar to values declared in the original publications) ranging from 32 to 86 drag counts on a mesh with 1024 points around the aerofoil.…”
Section: B Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Meheut [20] compared a number of optimised aerofoil shapes from six different institutes [4,5,7,13,14,16] with the same flow solver. This produced a range of final drag results (all similar to values declared in the original publications) ranging from 32 to 86 drag counts on a mesh with 1024 points around the aerofoil.…”
Section: B Previous Workmentioning
confidence: 99%
“…Due to the large range of factors influencing the results it is difficult to isolate contribution of the parameterisation method from these previous studies. For example, the choice of flow solver [16] or optimisation algorithm [14] has been shown to have a significant impact on the optimisation results for this case. For this reason this work tests this case with a large range of parameterisation methods under the same optimisation framework across a range of design variables.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these works found that single design point aerodynamic optimization lead to results with poor off-design performance and that multiple flight conditions must be considered to lead to a practical and robust design [24,28]. More recently, several optimization cases featuring multiple design conditions were also defined and solved [18,25]. These benchmark cases have been successful in getting practitioners from academia and industry to solve the same problem.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the AIAA Aerodynamic Design Optimization Discussion Group (ADODG) a was formed. As part of this, a number of inviscid and viscous aerofoil and wing optimization cases were suggested, with a number of research groups presenting results; see [13][14][15][16][17][18][19][20] for example.…”
Section: Introductionmentioning
confidence: 99%